PERBANDINGAN ISOLASI MINYAK ATSIRI DAUN NILAM (Pogostemon cablin Benth.) METODE HIDRODISTILASI KONVENSIONAL DAN HIDRODISTILASI OVEN MICROWAVE DISERTAI UJI AKTIVITAS ANTIMIKROBA - Jannah, Rahmi Miftahul; Zamri, Adel (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Microwave assisted hydrodistillation (MAHD) is the improvement of hydrodistillation (HD) technics which uses microwave energy as source in its refining process. The purpose of this research was to determine the best method of two extraction methods forpatchouli leaves (Pogostemon cablin Benth.). MAHD and HD methods have been compared and evaluated for its effectiveness to isolate the essential oil of fresh patchouli leaves. The results showed MAHD method offered a very important advantage exceeded HD within energy storage and isolation term. MAHD method took time for 1.5 hours whereas HD for 6 hours. The essential oil composition of extraction that determined by GC-MS. The main compounds of essential oil ofÂ  Patchouli leaves were patchouli alcohol with levels 53.00% HD and 53.10% MAHD. The density was 0.959 g/mL of HD and 0.963 g/mL of MAHD. Antimicrobial test showed te HD essential oil effectiveness was better than those of MAHD and teÂ  effectiveness on E.coli bacteria. However, the MAHD method was to be considered enviromental friendly.